Changes in injury type among NBA athletes in response to the COVID-19 pandemic - Cassinat, J.; Crowley, M.; Simpson, J.; Service, B. C. (The Physician and Sportsmedicine, 2024)
Context The 2019-2020 NBA season was altered significantly by the COVID-19 pandemic with a midseason suspension of games, the NBA `bubble` tournament, and a shortened offseason. Concerns were raised regarding player conditioning and the potential increased risk of injury due to the schedule changes. The purpose of this study was to determine the impact of the COVID-19 pandemic and associated schedule changes on NBA injuries. It was hypothesized that injury rates would be higher in the year following the pandemic and teams who participated in the bubble would have higher injury rates in the following season than non-bubble teams. Furthermore, the types of injuries would shift toward more severe injuries in the condensed 2019-20 season and the following 2020-21 season.